Peran Motivasi Terhadap Keterlibatan Karyawan - Habibah Asaria; Anwar Mansyur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the significance of the influence of intrinsic motivation and extrinsic motivation on employee engagement. This study uses sampling techniques with purposive sampling method, where the determination of sampling based on the criteria and the desired amount. The sample studied as many as 110 respondents. The stages of testing in this study are instrument test, model test, and hypothesis test using SPSS 25 Software. Based on the results of research shows intrinsic motivation and extrinsic motivation have a significant positive effect on employee engagement. With the motivation of the employees and the support of the company makes employees always involved in the work that can benefit the company. Keywords: Intrinsic Motivation, Extrinsic Motivation, Employee Engagement.